Research on Innovative Talent Training Mode under the Background of the Digital Economy (Journal of Interdisciplinary Insights, 2024)
Abstract: In the wave of the digital economy, the combination of traditional industries and emerging technologies has posed new challenges to talent training. This paper begins with an overview of the development trends of the digital economy and its impact on the education field, pointing out the new challenges facing education. Then, by analyzing the problems existing in the current talent training, this paper discusses the necessity of constructing an innovative talent training mode. Taking e-commerce and international commerce as an example, this paper proposes a series of future-oriented talent training strategies, including reforming the curriculum system, innovating teaching methods, strengthening school-enterprise cooperation, expanding international vision, and promoting interdisciplinary integration. These strategies aim to provide practical guidance and theoretical reference for higher education institutions to cultivate high-quality, compound, and innovative talents adapted to the era of the digital economy.